Single-cell electro-mechanical shear flow deformability cytometry - Junyu Chen; Xueping Zou; Daniel C. Spencer; Hywel Morgan (Microsystems & Nanoengineering)
Abstract The complex structural and molecular features of a cell lead to a set of specific dielectric and mechanical properties which can serve as intrinsic phenotypic markers that enable different cell populations to be characterised and distinguished. We have developed a microfluidic technique that exploits non-contact shear flow deformability cytometry to simultaneously characterise both the electrical and mechanical properties of single cells at high speed. Cells flow along a microchannel and are deformed (elongated) to different degrees by the shear force created by a viscoelastic fluid and channel wall. The electrical impedance of each cell is measured using sets of integrated microelectrodes along two orthogonal axes to determine the shape change and thus the electrical deformability, together with cell dielectric properties. The system performance was evaluated by measuring the electro-mechanical properties of cells treated in different ways, including osmotic shock, glutaraldehyde cross-linking and cytoskeletal disruption with Cytochalasin D and Latrunculin B. To confirm the accuracy of the system images of deformed cells were also captured using a camera. Correlation between the optical deformability and the electrical deformability is excellent. This novel cytometer has a throughput of ~100 cells s—1 is simple, does not use sheath flow or require high speed optical imaging.